The practice of "squatting" as a process of socialization to feminism within the Occupy Madrid squat movement of the 80s - Bergès, Karine (Hispania Nova, 2020)
Based on the studies that have been published on the political culture of the squat of the 1980s, this article aims to delve into the feminist militancy of the Madrid women squatters. Following the trajectory of a minority and radical group, LigaDura, founded in 1987, we will focus on the study of "squatting", as a practice of resistance against the neoliberal order and real estate speculation. If this form of mobilization proposes to develop other forms of life for a rebellious and rebellious youth, the analysis of "squatting", from a gender perspective, sheds light on the reproduction of a patriarchal culture in its midst, and at the same time, about the process of socialization to feminism that induces for women squatters.
Keywords: Squatting; Movimiento Okupa; feminism; patriarchy; socialization; LigaDura